Process of Perfection Method and Its Adaptability in EFL Classrooms of Nepal - Sherma, Amar (JET (Journal of English Teaching), 2023)
Teaching and learning are a never-ending process—a continuum. So, change is inevitable. Our practices, perspectives and assessment procedures must be changed in accordance with the changing law of nature. What was considered best yesterday may not remain best today. It is educators who need to keep themselves abreast of new methodologies, trends and discoveries to cater to the changing needs of students. This study attempts to illustrate how innovative and effective Process of Perfection (POP) method of teaching is and how this method can be adapted in our EFL classrooms to maximise the learning outcomes of students whose English language competence may or may not be high and classrooms may or may not be well-equipped with ICT tools and adequate number of teaching resources. 6 English language teachers and 40 students from the only private school that implemented POP method of Global Classroom curriculum were selected to survey the effectiveness and adaptability in the teaching of the English language. The researcher employed mixed-methods research to undertake the study where two different sets of questionnaires for both the teachers and the students were used to collect data. The findings demonstrated that advantages outnumbered disadvantages in a country like Nepal. Teachers want to use this teaching method because after having been acquainted with this method of teaching, they no longer have difficulty designing hands-on activities. Each textbook contains recommended activities that are designed according to the lesson. And this teaching method basically facilitates three types of learners: visual, auditory and kinaesthetic. The students also feel happy as this method is a joyful and effective learning process. However, they sometimes have difficulties grasping the concept of some English grammar lessons that are of higher level.